Et andet friluftsliv og en alternativ biologi - om abeforskning, spejdervæsen og woodcraft-folk - Eichberg, Henning (Forum for Idræt, 2004)
Artiklen beskriver bl.a. forskelle på spejder- og woodcraftbevægelserne og diskuterer friluftsliv ud fra den grundantagelse, at friluftsliver bygger på mere end fysisk bevægelse. A different outdoor life and an alternative biology: on primate research, the nature of scouting, and woodcraft folk. Outdoor life is not only a complex of physical activities, as the term ‘scouting sports’ may have us believe. Outdoor activities are connected with concepts of nature and with certain forms of knowledge that are also fundamental to the natural sciences. This article approaches this complex relation through the biography of the animal. Since the 1960s biologists have used fieldwork to “discover” and reconstruct the life histories of chimpanzees. The significance of these biographies for biological research is that they open the way for a revision of scientific method. And they allow a fresh retrospective look at scouting history. The Boy Scouts movement was started around 1900-1910 by Ernest Thompson Seton, an American author of animal novels, and the British military officer Lord Baden-Powell. The two founder figures represented different ways of relating to nature. The multiplicity that existed between the role models of “the soldier” and the “Red Indian” can also be found in early Danish scouting, where different emphases were placed by Cay Lembcke and by Hans Hartvig-Møller. The practical choice between “war in nature” and “peace with nature” was linked to contradictions in the understanding of nature. Nature was an arena on the one hand for struggle for the survival of the fittest – on the other for dialogue with the animal as ‘the other’.